Informal Islamic Education and its Role in Human Resource Development in Society: A Theoretical Evaluation - Alam, Kamiz Uddin Ahmed; Muzahid, Mohammad Aman Uddin (IIUC Studies, 2009)
This article attempts to focus on Islamic education in the informal setting, its correspondence with human resource development and the role of this development to create a sound and balanced environment in society with moral and spiritual values. Firstly, the paper addresses education and its function in general and then education from Islamic perspective. Secondly, it discusses the character of informal Islamic education, the role players of the field of informal Islamic education, their status as teachers, the role of a teacher, the competencies of a teacher, and teacher - learner relationship in the light of Islamic culture and heritage. Finally, a proposal on the specific subject of Informal Islamic education and the strategies of imparting it are presented in the article. doi: 10.3329/iiucs.v3i0.2667 IIUC STUDIES Vol. - 3, December 2006 (p 83-92)